Factors affecting health seeking behavior of elderly people residing in a community of Pokhara, Nepal. - Acharya, Anita (2021)
ABSTRACT: Introduction: Elderly people have different opinion regarding willingness to seek health care services and it is influenced by many factors. Thus, this study aims to find out the factors affecting health seeking behavior among elderly people. Methods: Cross-sectional analytical study was conducted among 197 elderly people of 65 years and above in Pokhara Metropolitan City ward No.28. Non probability purposive sampling technique was used. Data was collected by face to face interview technique using self-developed structured interview schedule. SPSS 16 was used for data analysis. Analysis was done by using descriptive and inferential statistics. The association between two variables was measured by Chi- square considering p- value < 0.05 as statistically significant. Results: Findings revealed 77.66% of respondents sought appropriate health care where as 22.34% of respondents sought inappropriate health care. The factors associated with health seeking behaviour were assessed using Andersen's behavioral model. Among selected factors accompany for the treatment of elderly people was found to have significantly associated with health seeking behaviour. (p= 0.040) Conclusion: More than two third of the respondents reported seeking appropriate health care and nearly one fourth reported seeking inappropriate health care. Among them, nearly two third of respondents sought care from governmental health facilities followed by private health facilities. Among the respondents whose health seeking behaviour was inappropriate, still more than one third respondents used self-treatment by home remedy. Key words: Elderly people, Health seeking behaviour,Nepal